2015
DOI: 10.3390/rs70608045
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Pasture Quality of Fresh Vegetation Based on Spectral Slope of Mixed Data of Dry and Fresh Vegetation—Method Development

Abstract: Abstract:The main objective of the present study was to apply a slope-based spectral method to both dry and fresh pasture vegetation. Differences in eight spectral ranges were identified across the near infrared-shortwave infrared (NIR-SWIR) that were indicative of changes in chemical properties. Slopes across these ranges were calculated and a partial least squares (PLS) analytical model was constructed for the slopes vs. crude protein (CP) and neutral detergent fiber (NDF) contents. Different datasets with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 48 publications
3
25
0
Order By: Relevance
“…Begley et al [20] detected differences in the absorption bands of water at 1806 nm that were well correlated with different concentrations of NaCl in meat. A similar relationship between the total area of water absorption and crude protein content was found by Lugassi et al [35].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Begley et al [20] detected differences in the absorption bands of water at 1806 nm that were well correlated with different concentrations of NaCl in meat. A similar relationship between the total area of water absorption and crude protein content was found by Lugassi et al [35].…”
Section: Discussionsupporting
confidence: 86%
“…For example, to obtain 50% accuracy, we need a sample size of 103 spectral measurements, whereas to obtain 90% accuracy, 286 measurements are needed. Taking into account all of the above, we can argue that in order to achieve a higher accuracy of salinity estimation, future studies should be expanded and include the following steps: (1) using the dataset with the much wider range of chemical reference values and vegetation types; (2) larger calibration and validation dataset samples; and (3) incorporating multiple slopes into the analyses (similarly to Lugassi et al [35]). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the same spectra and similar modelling approaches could be used in further studies for quantification of other important biorefinery constituents of Ulva biomass, such as starch, proteins, pigments and special chemicals. For example, Lugassi et al (2015b) concluded that crude protein and neutral detergent fibre contents could be predicted using the spectral slope method for dry and wet vegetation.…”
Section: Exploratory Assessment Of the Potential Of Spectral-based Chmentioning
confidence: 99%